Heat and mass transfer in the melting of frost - Mohs, William F.; Kulacki, F. A. (Springer International Publishing, 2015)
This Brief is aimed at engineers and researchers involved in the refrigeration industry: specifically, those interested in energy utilization and system efficiency. The book presents what the authors believe is the first comprehensive frost melting study involving all aspects of heat and mass transfer. The volume?s description of in-plane and normal digital images of frost growth and melting is also unique in the field, and the digital analysis technique offers an advantage over invasive measurement methods. The scope of book?s coverage includes modeling and experimentation for the frost formation and melting processes. The key sub-specialties to which the book are aimed include refrigeration system analysis and design, coupled heat and mass transfer, and phase-change processes.